Macro- and Micro-Climatic Influence on Maize Quality and Insect Pest Management Strategies in Small Market Storehouses in Nigeria - Omobowale, Mobolaji Oluyimika; Kolayemi, Olumuyiwa Rapheal; Olenloa, Akhere Eromosele; Ogwumike, Jonathan C.; Ala, Adeola Adefoluke; Omodara, Michael A.; Busari, Gbenga S.; Braimah, Jafar A.; Ajao, Shekinat Kehinde; Otitodun, Grace Olufunke; Nwaubani, Samuel I.; Ileleji, Klein E.; et al. (Discoveries in Agriculture and Food Sciences, 2024)
Weather plays a major role in the microclimate of grain storage facilities and could impact the quality of stored grain, most especially in the humid tropics where weather conditions are favorable to insect and mold formation. This study compared the influence of macro and microclimates — temperature and relative humidity (RH) in six storehouses located in three grain markets in Ibadan, Oyo, and Ilorin, Nigeria. The study was conducted from February–December 2016. Traditional Storage Practice (TSP) and Integrated Pest Management (IPM) were used in each of the markets. The average size of each storehouse was 4 m × 2.5 m × 2.5 m and each had twenty-five 100-kg polypropylene bags of maize stacked singly (not nested) in five columns. 15 bags were randomly sampled monthly for moisture content (MC) and insect counts using standard methods. Temperature and RH of the ambient and in-between grain stack were recorded using data loggers. Mean temperatures and RH for ambient, stack, and grain ranged from 29.3–30.80C and 53.9–59.4% for the storage period. Mean insect count for the six storehouses with IPM and TSP were 1.4 and 7.6 in 700 g per bag, respectively. Ambient conditions correlated with grain stack temperature in all storehouses. MC of stored maize was not significantly affected by the location of storehouses and storage practices. However, insect population was significantly affected by storage practices. Proper grain storage management play a major role in maintaining grain quality during the storage. Commercial grain aggregators are advised to adopt the IPM strategies and ensure regular monitoring of the microclimates of bagged grain to reduce storage losses.